2013
DOI: 10.3109/13880209.2013.790065
|View full text |Cite
|
Sign up to set email alerts
|

Study on hemostatic activities of the rhizome ofParis bashanensis

Abstract: Context: Paris bashanensis Wang et Tang (Liliaceae) is widely used in traditional Chinese medicine for the treatment of injuries, fractures and hemorrhage in Hubei and Sichuan Province. Objective: The n-BuOH extract of Paris bashanensis was investigated for hemostatic activity and chemical constituents in order to provide a basis for the application in folk use. Materials and methods:The n-BuOH extract of P. bashanensis was divided into three eluents (30, 50 and 70% EtOH) by macroporous adsorptive resin D101. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…They could reflect the whole process of blood coagulation since blood was eluted from the micrangium (Li et al, 2008). In our study, PY as the standard herbal medicine showed the hemostatic activity by reducing the values of bleeding time and clotting time, which was consisted with the reported (Wu et al, 1987;Wang et al, 1989). The other five species of Paris L. (PD, PF, PB, PM, and PP) could also shorten the values of bleeding time and clotting time in mice significantly, and PD, PB and PP showed more effective than the other groups.…”
Section: Discussionsupporting
confidence: 78%
“…They could reflect the whole process of blood coagulation since blood was eluted from the micrangium (Li et al, 2008). In our study, PY as the standard herbal medicine showed the hemostatic activity by reducing the values of bleeding time and clotting time, which was consisted with the reported (Wu et al, 1987;Wang et al, 1989). The other five species of Paris L. (PD, PF, PB, PM, and PP) could also shorten the values of bleeding time and clotting time in mice significantly, and PD, PB and PP showed more effective than the other groups.…”
Section: Discussionsupporting
confidence: 78%
“…It's worth noting that TSTT are mainly constituted by two kinds of steroidal saponins, pennogenin, and diosgenin saponins, which possess different biological and pharmacological properties (Hernandez-Vazquez et al, 2020;Ahmad et al, 2021). Specifically, pennogenin saponins have antiinflammatory, anti-tumor and anti-hemorrhagic activity (Wang et al, 2013). For example, Paris saponin VII showed robust effect of anti-inflammation in LPS-stimulated RAW264.7 cells by reducing the levels of pro-inflammatory cytokines and enzymes, simultaneously inhibited the inflammation response to ear edema and granuloma formation in mice (Zhang C. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The average time of each observation was 20 s. The collected blood samples were also spotted on glass slides and clotting times determined. Clotting was achieved when the fibrin mesh appeared and could be picked by glass dissecting needle [47,48].…”
Section: Methodsmentioning
confidence: 99%